2018
DOI: 10.3389/fnbeh.2018.00159
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Deprivation Increases Anxiety- and Depressive-Like Behaviors in an Age-Dependent Fashion and Reduces Neuropeptide Y Expression in the Amygdala and Hippocampus of Male and Female Young Adult Rats

Abstract: Maternal deprivation for 24 h produces an immediate increase in basal and stress-induced corticosterone (CORT) secretion. Given the impact of elevated CORT levels on brain development, the goal of the present study was to characterize the effects of maternal deprivation at postnatal days 3 (DEP3) or 11 (DEP11) on emotional behavior and neuropeptide Y immunoreactivity (NPY-ir) in the basolateral amygdala (BLA) and dorsal hippocampus (dHPC) of male and female rats. Litters were distributed in control non-deprive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 109 publications
(127 reference statements)
1
34
1
Order By: Relevance
“…Moreover, a dose response relationship between intranasal NPY and anxiety has been reported at higher doses of NPY, without significant side effects in animals (Sabban & Serova, ). Animal studies suggest that lower NPY levels are associated with depressive, anxiety‐like, and PTSD symptoms (Cohen et al, ; Miragaia et al, ). And, some pro‐depressant agents cause a drop in NPY (Desai, Borkar, Nakhate, Subhedar, & Kokare, ), which in turn is increased by antidepressants (Kotagale, Paliwal, Aglawe, Umekar, & Taksande, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a dose response relationship between intranasal NPY and anxiety has been reported at higher doses of NPY, without significant side effects in animals (Sabban & Serova, ). Animal studies suggest that lower NPY levels are associated with depressive, anxiety‐like, and PTSD symptoms (Cohen et al, ; Miragaia et al, ). And, some pro‐depressant agents cause a drop in NPY (Desai, Borkar, Nakhate, Subhedar, & Kokare, ), which in turn is increased by antidepressants (Kotagale, Paliwal, Aglawe, Umekar, & Taksande, ).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive literature indicates that there are sex differences in the NPY system in relation to stress within both the central nervous system and periphery [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. In order to better understand its role in different biological processes, it is imperative to investigate NPY’s actions in a sex-specific manner.…”
Section: Stress-protective Effects Of Npymentioning
confidence: 99%
“…However, when animals exposed to early-life stress were examined in adolescence, females tended to exhibit lower NPY expression in specific brain regions. Specifically, these females showed fewer NPY-immunoreactive neurons than males in both the basolateral amygdala and the hippocampus after exposure to maternal separation stress [ 66 ]. Furthermore, adult female rats had lower NPY peptide levels in the dorsal hippocampus after maternal separation stress than males [ 67 ].…”
Section: Sex Differences In Brain-specific and Peripheral Npy Exprmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that animals or human beings that are in a state of social isolation for a long time will exhibit depressive-like behavior (Evans IEM et al, 2017;Kosofsky BE et al, 1987;Ge L et al, 2017;Chow PI et al, 2017;Li X et al, 2013). It is known that depressive-like behavior is related to abnormal brain development, abnormal serotonin levels, and neuroinflammation (Miragai AS et al, 2018;Xin F et al, 2018;Han L et al, 2018). However, the mechanism of depressive-like behavior induced by social isolation stress has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%